2015
DOI: 10.1002/stem.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reprogramming Allows Generation of Autologous Hematopoietic Progenitors From AML Patients That Are Devoid of Patient-Specific Genomic Aberrations

Abstract: Current treatments that use hematopoietic progenitor cell (HPC) transplantation in acute myeloid leukemia (AML) patients substantially reduce the risk of relapse, but are limited by the availability of immune compatible healthy HPCs. Although cellular reprogramming has the potential to provide a novel autologous source of HPCs for transplantation, the applicability of this technology toward the derivation of healthy autologous hematopoietic cells devoid of patient-specific leukemic aberrations from AML patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
(75 reference statements)
1
18
0
1
Order By: Relevance
“…In agreement with Salci et al [1], we also found that only "healthy" patient-specific iPSCs were generated from AML patient cells. Both studies support the idea that the reprogramming process may be biased against certain leukemiaspecific genetic aberrations.…”
Section: Cd66bsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with Salci et al [1], we also found that only "healthy" patient-specific iPSCs were generated from AML patient cells. Both studies support the idea that the reprogramming process may be biased against certain leukemiaspecific genetic aberrations.…”
Section: Cd66bsupporting
confidence: 93%
“…None of the known leukemiaassociated genetic aberrations present in four primary AML samples was detected in any of the corresponding patient-specific iPSC or HPCs differentiated from iPSC clones [1]. This work represents an exciting advance for the field of autologous transplantation in AML treatment, especially considering the reduced risk of transplanting leukemia cells back into the patient.…”
Section: Significance Statementmentioning
confidence: 88%
See 1 more Smart Citation
“…Upon thawing, CD34+ enrichment was performed using human CD34 MicroBead Kit (Miltenyi Biotec, Bergisch Gladbach, Germany) and then AML samples were cultured in hematopoietic medium: Iscove's Modified, Dulbecco's Media (IMDM) with 15% v/v BSA (Bovine Serum Albumin), Insulin, and Transferrin (BIT) (StemCell Technologies Vancouver, Canada), 1% v/v Non‐Essential Amino Acids (NEAA), and 1% v/v Na‐pyruvate (Gibco, Grand Island, NY), 100 ng/ml Flt‐3 ligand, 20 ng/ml interleukin‐3, and 100 ng/ml thrombopoietin (all (R&D Systems, Minneapolis, MN)) and 100 ng/ml stem cell factor (Amgen Inc., Thousand Oaks, CA) for 24 to 48 hours before transduction. During reprogramming, AML samples were cultured on irradiated mouse embryonic fibroblasts (iMEFs) in reprogramming media supplemented either with 10 ng/ml human fibroblast growth factor (FGF) 2 (R&D systems), or 20 ng/ml human leukemia inhibitory factor (LIF, ThermoFisher), PD0325901 (1 μM), and CHIR99021 (3 μM, (Selleckchem, Houston, TX)), herein termed FGF 2 and LIF‐2i media , respectively. iPSCs were differentiated into hematopoietic progenitor cells (HPCs) as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence in situ hybridization was performed on AML, iPSC, and colony‐forming unit (CFU) samples, as described previously . Number of nuclei scored is indicated in figure legends.…”
Section: Methodsmentioning
confidence: 99%